The Duality of Administrative and Communicative Powers in Legislative Drafting: Evidence from East Java - Bagijo, Himawan Estu; Siboy, Ahmad; Al-Fatih, Sholahuddin; Affan, Mohammad (Universitas Negeri Semarang, 2024)
The classical legal concept within executive and legislative scopes is no longer adequate to help understand the strategic measures taken by the Provincial Government of East Java and the potential of communicative actions of the DPRD of the Province of East Java. The making of autonomous regulations tends to be exclusive and overlooks the involvement of the public as the origin from which the procedures of legislative drafting began. The legal thought introduced by Habermas came as a solution to legislation-related issues, but it seems to be accepted only by the dialogue between legislators and the executive body. This article aims at analyzing the interaction that takes place between discourse theory and the duality of administrative and communicative powers by Habermas relating to the strategic measures taken by the Provincial Government of East Java. A normative-juridical method was used, involving the literature study of legal concepts and the data revealing the performance of the Legal Bureau of the Provincial Government of East Jav a. Communicative measures exist in the construction of autonomous regulations while facilitating measures and evaluations of autonomous regulations set by the regency or municipality represent a strategic example.